Real-Time Analysis of Endogenous Wnt Signalling in 3D Mesenchymal Stromal Cells - Fatima Saleh; Alice Carstairs; S. Leah Etheridge; Paul Genever (Stem Cells International)
Wnt signalling has been implicated in the regulation of stem cell self-renewal and differentiation; however, the majority of in vitro studies are carried out using monolayer 2D culture techniques. Here, we used mesenchymal stromal cell (MSC) EGFP reporter lines responsive to Wnt pathway activation in a 3D spheroid culture system to mimic better the in vivo environment. Endogenous Wnt signalling was then investigated under basal conditions and when MSCs were induced to undergo osteogenic and adipogenic differentiation. Interestingly, endogenous Wnt signalling was only active during 3D differentiation whereas 2D cultures showed no EGFP expression throughout an extended differentiation time-course. Furthermore, exogenous Wnt signalling in 3D adipogenic conditions inhibited differentiation compared to unstimulated controls. In addition, suppressing Wnt signalling by Dkk-1 restored and facilitated adipogenic differentiation in MSC spheroids. Our findings indicate that endogenous Wnt signalling is active and can be tracked in 3D MSC cultures where it may act as a molecular switch in adipogenesis. The identification of the signalling pathways that regulate MSCs in a 3D in vivo-like environment will advance our understanding of the molecular mechanisms that control MSC fate.